Transition from university to industry: challenges faced by new engineers in the automotive industry / Chan Yuen Fook and Selvam Balaraman - Chan, Yuen Fook; Balaraman, Selvam (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
The Malaysian automotive manufacturing industry is growing exponentially, but it faces shortage of the right skilled automotive manufacturing professionals to propel the industry to an unprecedented height. This research hypothesised that there are several challenges faced by new engineers in executing daily task due to knowledge gap. New engineers are not guided and trained sufficiently to undertake daily task to be more productive. Therefore, this research aims to identify the knowledge gap and challenges faced by new engineers in the automotive company in Malaysia. The scope of this research is confined to the theories of Human Capital, which relate to the capabilities and skills of an employee to improve job performance. A qualitative case study method has been employed for the analysis and comparison of data from public and private universities and automotive manufacturing industry in Malaysia. The identified target groups were human resource manager, manufacturing managers, new engineers and lecturers. This study concludes that training in industry has failed at certain aspects to produce new employees that meet current competency requirements, lead to the deterioration of employee work performance. In conclusion, this research validates the existence of a knowledge gap and acknowledges the need to overcome challenges faced by new engineers during their transition from academia to industry.